On the transformative potential of Hungarian local food-buying clubs - Benedek, Zsófia (Frontiers in Sustainable Food Systems, 2023)
This study describes the development trends of local food-buying clubs (BCs) in Hungary and analyses how this type of grassroots initiative can contribute to the sustainability transition. BC are consumer-driven organizations which aim to connect local food producers with consumers. The study also discusses how the Hungarian implementation differs from other initiatives described in the literature. The empirical analysis employs qualitative techniques, including participant observation, in-depth interviews with three organizers and two external experts, and a survey of 82 BC producers. BCs may be instrumental in facilitating the sustainability transition: on the one hand, they reach a wide range of consumers, and on the other, they are in contact with a multitude of producers, so everything is in place for their successful scaling up, with a particular focus on the maintenance of core values. BCs can thus play an instrumental role in influencing attitudes and fostering community. One of their most significant advantages is that, while they can operate independently of the growth imperatives of the dominant capitalist paradigm, they can also be understood within it. The increase in the number of grassroots initiatives has led to the formation of a meta-organization aimed at generating and sharing knowledge and the joint utilization and development of specific resources, such as information technologies. The variety of organizational forms and operating modes allows the general approach of buying clubs to be tailored to specific micro-contexts. However, there is a potential danger associated with the large proportion of volunteer work. For BCs to be successful over the long term, it is vital that they are self-sufficient in terms of everyday economic activities and that organizers are at least partially compensated for their efforts.